Discourse critical analysis of the Dictatorship educational policy (1967-1974) about the Greek-speaking education of the Greeks abroad - Kalerante, Evaggelia (International Journal of Language, Translation and Intercultural Communication, 2015)
The present paper is concerned with the Dictatorship legislative texts (1967-1974) related to issues about the Greek-speaking education of the Greeks abroad. The legislative texts about education are presented as discourse in which the cultural and political practice is articulated; and is also composed by other cultural and political practices conducive to its dialectic association with other dimensions of society. The critical analysis of the Dictatorship legislative texts focuses on the discourse verbal practices and the ideological scenario. Thus, an attempt is made to depict: a) discourse practices and b) broader social and political structures and standpoints in the legislation which are related to the broader theoretical frameworks of the democratic regime and, particularly, special issues about the nation-state definition. The fact that should definitely be made obvious is how the discourse practices in legislation are conducive to the reproduction of political-educational standpoints of the Greek nation-state in association with the Greek population abroad on the basis of a broader political framework of dictatorship. Norman Fairclough’s discourse critical analysis was chosen because there is interest in: the linguistic characteristics of the text and how they are attuned to the regime’s political practice. Therefore, throughout the discourse educational levels, in which legislation is introduced, the regime’s structure of ideology is elevated.